The Humble Charisma of a White-Dressed Man in a Desert Place: Pope Francis’ Communicative Style in the Covid-19 Pandemic - Scardigno, Rosa; Papapicco, Concetta; Luccarelli, Valentina; Zagaria, Altomare Enza; Mininni, Giuseppe; D’Errico, Francesca (Frontiers in Psychology, 2021)
The context of deep uncertainty, fear and “social distancing” characterising the COVID-19 pandemic has led to a need for cultural anchorages and charismatic leaders who may conjointly and effectively support human beings, strengthen their identity as well as empower social commitment. In this perspective, Pope Francis’ charismatic leadership, which is widely shared not only within the religious world, may play a crucial role in facing emergency with existential reasons and psychological resources. The general aim of this work is to shed light on the communicative features of Pope Francis’ charismatic leadership during the pandemic emergency: in order to better understand his effectiveness, we analysed both the core issues and his multimodal body signals in the global TV event of the Universal Prayer with the Urbi et Orbi Blessing. The multimodal and discursive analysis of the homily enabled us to define the Pope’s “humble” charisma which is based upon on authentic and informal presence, manifested emotional signals (and, in particular commotion) showing features of equity and familiarity. From a discursive point of view, the common and overarching affiliation is constructed through a multiple focus on the “we” pronoun, which is constructed through socio-epistemic rhetoric. The results show how this integrated methodological perspectives – i.e. multimodal and discursive – may offer meaningful pathways detection of effective and persuasive signals.